Forward genetic screens identified mutants with defects in trap morphogenesis in the nematode-trapping fungus Arthrobotrys oligospora. Issue 2 (30th December 2020) - Huang, Tsung-Yu; Lee, Yi-Yun; Vidal-Diez de Ulzurrun, Guillermo; Hsueh, Yen-Ping
Abstract: Nematode-trapping fungi (NTF) are carnivorous fungi that prey on nematodes under nutrient-poor conditions via specialized hyphae that function as traps. The molecular mechanisms involved in the interactions between NTF and their nematode prey are largely unknown. In this study, we conducted forward genetic screens to identify potential genes and pathways that are involved in trap morphogenesis and predation in the NTF Arthrobotrys oligospora. Using Ethyl methanesulfonate and UV as the mutagens, we generated 5552 randomly mutagenized A. oligospora strains and identified 15 mutants with strong defects in trap morphogenesis. Whole-genome sequencing and bioinformatic analyses revealed mutations in genes with roles in signaling, transcription or membrane transport that may contribute to the defects of trap morphogenesis in these mutants. We further conducted functional analyses on a candidate gene, YBP-1, and demonstrate that mutation of that gene was causative of the phenotypes observed in one of the mutants. The methods established in this study might provide helpful insights for establishing forward genetic screening methods for other non-model fungal species.